Effect of using high molecular weight crosslinker on the physical properties of super porous hydrogel composite (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2023)
Superporous hydrogel composite is widely utilized and investigated as a gastro retentive drug delivery system. Materials used in Superporous hydrogel formulation have a profound effect on its properties’, N-methylene bisacrylamide is the crosslinker of choice for the preparation of SPH.The purpose of this study is to determine if using a new high molecular weight crosslinker such as polyethylene glycol diacrylate will affect the physical characteristics of SPH and drug release behavior. For the preparation of super porous hydrogel polyvinyl alcohol, acrylamide, polyethylene glycol diacrylate 700, N, N-Methylene bisacrylamide, sodium bicarbonate, and tween 20 were used. Trifluoperazine HCl was used as a model drug. The buoyancy, porosity, density, drug release, drug content, swelling ratio, and swelling time were studied and compared. All the physical characteristics and medication release profiles were impacted by changing the formulation parameters. The formula with the best physical qualities had 300 µl of acrylamide (40 percent w/v), 20 mg of polyvinyl alcohol, 200 µl of Tween 20 (v/v), 5 µl of polyethylene glycol diacrylate 700, 45 µl ammonium persulfate, 45 µl TEMED and 50 mg of sodium bicarbonate. Around 80% of the drug was released over the course of 12 hours according to zero order kinetics. By modifying the formulation parameters using polyethylene glycol diacrylate, Superporous hydrogel was successfully manufactured and has the best properties to be employed as a gastro retentive drug delivery system.